Alveolar cytokines and interferon autoantibodies in COVID-19 ARDS - Jonassen, Trine B.; Jørgensen, Sofie E.; Mitchell, Nikki H.; Mogensen, Trine H.; Berg, Ronan M. G.; Ronit, Andreas; Plovsing, Ronni R. (Frontiers in Immunology, 2024)
Background: Type I interferons (IFN-I) and IFN autoantibodies have a crucial role in controlling SARS-CoV-2 infection. Levels of these mediators have only rarely been studied in the alveolar compartment in patients with COVID-19 acute respiratory distress syndrome (CARDS), but has not been compared across different ARDS etiologies, and likewise the potential effect of dexamethasone (DXM) on these mediators is not known.We assessed the integrity of the alveolo-capillary membrane, interleukins and type I, II and III IFNs and IFN autoantibodies by studying epithelial lining fluid (ELF) volumes, alveolar concentration of protein and ELF-corrected concentrations of cytokines in two patient subgroups and controls.Results: 16 patients with CARDS (4 without and 12 with DXM treatment), 8 with non-CARDS and 15 healthy controls were included. Highest ELF volumes and protein levels were observed in CARDS. Systemic and ELF-corrected alveolar concentrations of interleukin (IL)-6 appeared to be particularly low in CARDS patients receiving DXM, whereas alveolar levels of IL-8 were high regardless of DXM treatment. Alveolar levels of IFNs were similar between CARDS and non-CARDS patients, and IFNα and IFNω autoantibody levels were higher in CARDS and non-CARDS patients than in healthy controls.Conclusions: CARDS patients exhibited greater alveolo-capillary barrier disruption with compartmentalization of IL-8, regardless of DXM treatment, whereas systemic and alveolar levels of IL-6 were lower in the DXM treated subgroup. IFN-I autoantibodies seem higher in BALF of CARDS patients, independently of DXM, whereas IFN autoantibodies in plasma were similar to controls.